Wisata Bersepeda sebagai Wisata Warisan Budaya yang Berkelanjutan di Yogyakarta - Wachidah, Inas Amatullah El; Prasodjo, Tjahjono (Department of Archaeology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
Over the past five years, cycling tourism has seen significant development as part of sustainable tourism, including in Yogyakarta. Its popularity has also expanded into the heritage-based tourism sector, with the utilization of Cultural Heritage Areas as one of the attractions for cycling tourism. This paper aims to address how how cycling tourism in heritage areas can be carried out sustainably. Data collection methods included observation, literature review, and interviews. Observations of cycling tourism practices were conducted through a case study approach. The frameworks of Heritage Tourism Sustainability and Transformative Experience Tourism were used to analyze and interpret the data collected and the presented case study. The conclusions indicate that cycling tourism in heritage areas, which is gaining popularity in Yogyakarta, can be optimized as a heritage tourism product capable of maintaining sustainability, both for cultural heritage sites and for the communities living around them, by adhering to key principles derived from this study as well as considering challenges that may arise in its development. === Dalam lima tahun terakhir, wisata bersepeda telah mengalami perkembangan yang signifikan sebagai bagian dari pariwisata berkelanjutan, termasuk di Yogyakarta. Popularitas wisata bersepeda juga meluas ke sektor pariwisata berbasis warisan budaya, dengan pemanfaatan Kawasan Cagar Budaya sebagai salah satu daya tarik wisata bersepeda. Tulisan ini berupaya menjawab bagaimana wisata sepada di kawasan cagar budaya dapat dilakukan secara berkelanjutan (sustainable). Metode pengumpulan data dilaksankan melalui observasi, studi pustaka dan wawancara. Pengamatan praktik wisata bersepeda diperoleh melalui studi kasus. Pendekatan Heritage Tourism Sustainability dan Transformative Experience Tourism digunakan untuk menganalisis dan menginterpretasikan data yang diperoleh dan terhadap studi kasus yang disajikan. Kesimpulan yang didapatkan menyatakan bahwa wisata bersepeda di kawasan cagar budaya yang semakin populer di Yogyakarta dapat dioptimalkan menjadi produk wisata warisan budaya yang mampu menjaga keberlanjutan, baik dari sisi objek cagar budaya maupun masyarakat yang tinggal di sekitarnya, dengan mempertimbangkan beberapa prinsip kunci hasil dari kajian ini serta tantangan yang mungkin dihadapi dalam proses pengembangannya.